Violating the Rules of Centralized Management of Technical Means of Counteracting the Threats to Information Security - E. A. Russkevich (Journal of Digital Technologies and Law, 2023)
Objective: to acquire new knowledge about the liability for violating the rules of managing technical means of counteracting the threats to information security; to elaborate theoretical recommendations and proposals for improving legislation and law enforcement.Methods: the methodological basis of the research is a set of scientific cognition methods, including abstract-logic, dogmatic, comparison, etc.Results: based on studying documents and publications, the following conclusions were made: 1) the measures taken at the national level for regulating the relations associated with introduction of technical means of counteracting the threats generally comply with the provisions of the Doctrine on information security of the Russian Federation; 2) one of the main directions of development of the foreign legislation on telecommunications is building a system of public-private interaction, in which communication operators would perceive the information security problem not as their internal task but as an element of the overall security of the state. In this regard, one may clearly trace the statement of the need to efficiently control the activities of communication operators, first of all, in the sphere of the newly introduced standards providing cyber resilience; 3) regulation of relations in the sphere of managing the technical means of counteracting threats in Russia is characterized by their multiplicity, multi-leveledness, hence, rather predictable complexity; 4) the model of communication operators’ liability for violations in the field of exploitation of technical means of counteracting threats, implemented in Article 274.2 Of the Russian Criminal Code, is not optimal. Rather disputable is the approach to describing the administratively prejudicial elements of crime. Despite the significance of the relations, the possibility of a criminal-legal reaction to a particular incident appears not in connection with the occurrence of certain publicly dangerous consequences and not even with the traditional recurrence, but only with the third documented violation. We consider more preferable the model of criminalization of violating the management of technical means of counteracting threats depending on infliction of substantial harm to the rights and legal interests of citizens or organizations, or the legally protected interests of the society or the state.Scientific novelty: the novelty of the research is mainly due to the actual underdevelopment of the issues related to the legal definition and implementation of criminal liability for violating the rules of centralized management of technical means of counteracting the threats to sustainability, security and integrity of functioning of the telecommunication network Internet and the general purpose communication network in the territory of the Russian Federation.Practical significance: the main provisions and conclusions of the research can be used for improving the mechanism of criminal-legal protection of information security, further development of the Russian doctrine of criminal law on liability for crimes in the sphere of computer information.